Energy security of Ukraine - Romanyuk, Natalia (Східноєвропейський національний університет імені Лесі Українки, 2020)
The article analyzes theoretical approaches to understanding the concept of «energy security». The main indicators of the level of energy security of Ukraine are described. The level of supply of energy resources of Ukraine is given. The development of spheres of the fuel and energy complex: gas industry, coal industry, oil industry and electric power industry is analyzed. The main threats to Ukraine’s energy security are defined as: low level of own energy resources availability; excessive dependence on energy imports; insufficient level of energy and technologies diversification of supply sources, high level of energy intensity of production and use of energy resources by municipal services. The main normative legal documents concerning the energy security of Ukraine are analyzed. The Energy Security Strategy of Ukraine till 2035 is outlined. The state policy instruments for preventing threats to Ukraine’s energy security are identified. The main tasks for ensuring energy security of Ukraine are defined: ensuring energy independence; formation of a conscious and energy efficient society; creation of competitive markets for gas, coal, oil and oil products, electricity and competitive conditions for their transportation through the territory of Ukraine; creating conditions for investment attractiveness of the energy sector of Ukraine; integration of gas and electricity markets and relevant transport networks of Ukraine into the energy space; decarbonisation of the energy sector; introduction of an effective system of strategic management in the sectors of the fuel and energy complex of Ukraine. The further development of fuel and energy sectors of Ukraine is forecasted. The approaches to ensure Ukraine’s energy independence and improve the investment climate in Ukraine’s energy sector are proposed. The development of the sectors of the fuel and energy sector of Ukraine is forecasted and approaches to ensuring the energy independence of Ukraine and improving the investment climate in the energy sector of Ukraine are proposed. It is determined that the level of reducing the energy intensity of the economy, diversification of sources and ways of energy supply and increasing their domestic production will increase not only energy but also economic and environmental security, which will optimize the energy balance and create a solid foundation for sustainable energy future of Ukraine.
Енергетична безпека України
Keywords: energy security; energy efficiency; Ukraine; energy; resources